GE_GERICHTE P/19362/2020 vom 5. Februar 2021 - GE Cour de justice (2021)
LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;TENTATIVE(DROIT PÉNAL);MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);CONTRAINTE SEXUELLE;VIOL;ASSISTANCE JUDICIAIRE | CPP.310; CP.123; CP.126; CP.105.al2; CP.180; CP.181; CP.189; CP.190; CPP.136